Examining the intersection of circular economy, forestry, and international trade - Gopalakrishnan, Badri Narayanan; Duggal, Taranjeet, 1974-; Tewary, Tavishi, 1984- (Advances in finance, accounting, and economics (AFAE) book series., 2021)
"This book examines the intersection of circular economy, forestry, and international trade"--